Wireless Network Security: Theories and Applications - Chen, Lei; Ji, Jiahuang; Zhang, Zihong (Springer Berlin / Heidelberg, 2013)
This book offers comprehensive discussion of current wireless network security technologies, vulnerabilities and potential threats, introduces and explains corresponding security standards and protocols, and provides detailed solutions to security concerns.